Some pediatric problems of Australian Agorigines - Michael Gracey (Paediatrica Indonesiana, 1973)
Australia is generally considered one of the "developed" nations; technicalIy advanced, with high standards of living and health, and with one of the lowest infant mortality rates in the world. This is true for the vast majority of Australians who are of European origin, but not for those of aboriginal descent, the ethnic minority who are now recognized to have serious health problems resembling those typical of poorer communities in other parts of theworld.